COMPARING MENTAL LEXICON BETWEEN L1 AND L2 ON INTERMEDIATE EFL LEARNERS OF FOURTH SEMESTER STUDENTS AT STUDY PROGRAM OF ENGLISH, UNIVERSITAS BRAWIJAYA - PRATAMA, ADITYA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Psycholinguistics show that words are stored in the mental lexicon. In exploring the mental lexicon, WAT (Word Association Test) has been used by psycholinguists. The principle of WAT is that stimulus words are presented to the subjects and then the subjects are asked to respond with the first word that appears in mind. There are three problems to be solved in this research, namely: (1) What types of word association are produced by intermediate EFL learners at Study Program of English; (2) What pattern emerges from the responses in L1 and L2 produced by those intermediate EFL learners; (3) What are the reasons of those intermediate EFL learners in choosing the responses. In this research, the researcher investigates the mental lexicon in intermediate EFL learners of fourth semester students at Study Program of English in Universitas Brawijaya. This research is expected to describe the comparison of mental lexicon between L1 and L2. Furthermore, It is expected to trigger the exploration of mental lexicon in Bahasa Indonesia. This research is classified as qualitative research. The type of qualitative research employed in this research is case study. The data were collected from 26 EFL learners from Study Program of English, Universitas Brawijaya. All subjects were asked to take a word association test which consists of eight stimulus words in Indonesia and eight stimulus words in English. Keywords: mental lexicon, first language, second language, word association test.